Crime, migration and data extraction: the Trump travel bans. (2018) - Guild, Elspeth
Three times in 2017 did the US Government issued orders banning nationals from some countries from entering the USA. The first two bans focused on nationals of Iran, Iraq, Libya, Somalia, Sudan, Syria and Yemen - with Iraq taken off the list in the March Order. The third measure of 24 September banned entry to most nationals of Chad, Iran, North Korea, Syria, Venezuela, Yemen and Somalia. These Orders were partially stopped by various US courts including appeal courts but partially lifted by the Supreme Court on 4 December 2017. This article examines the three travel bans from the perspective of the vocation of each of them to require all states to provide information regarding their citizens (and those foreigners about whom they hold information) to the US authorities in return for being left off the banned list.